(untitled) (Global Journal of Science Frontier Research, 2016)
Evaluation of varieties from different years in a common environment is the most direct of the several methods that have been used to estimate breeding progress. 33 tef varieties released in Ethiopia since 1970 till now were evaluated at DebreZeit and Melkassa Agricultural Research Centers to estimate the amount of genetic gain made over time in grain yield potential and associated characters. The varieties were laid out in a randomized complete block design with three replications in 2012 cropping season. Analysis of variance revealed significant differences among varieties for all traits except hundred seed weight on both locations.Grain yield was increased from 3848.68 kg ha -1 to 4934.4kg ha -1 over the past 42 years. The average annual rate of increase per year for the period of 1970-2012 was estimated from the linear regression of mean grain yield on year of variety release was 21.53 kg ha -1 with a relative genetic gain of 0.56% year -1 which was highly significantly different from zero.